The Urgency Of Authentication And Protection Of Personal Data In Online Transactions - Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2022)
Fraud in online trading is a crime that is difficult to enforce the law. Fraud can be committed by sellers by counterfeiting their products or by driving transactions outside of e-commerce. Meanwhile, fraud committed by buyers is carried out by falsifying identities and fake orders. The efforts have been made to threaten the perpetrators with criminal noose but have not reduced the number of frauds that occur. This research was conducted using normative research that looked at fraudulent behavior and related it to the legal provisions in the ITE Law and in the Personal Data Protection Law. The research found that the need for authentication as a marker for sellers and buyers when interacting on the internet so that fraud can be minimized because the identity of the perpetrator can be identified easily with the authentication method. So that the perpetrator's track record can be easily detected and this prevents the perpetrator from committing fraud.